Marcas de subjetividade em crônicas produzidas por alunos do PROEJA – IFPE - Lira, Eliane Angelim (2011)
This paper aimed at analyzing subjectivity marks in the chronicle genre produced by students of integrated technical courses of the National Programme for Integration of Basic Education with the Professional Education in the modality of Youth and Adults (PROEJA), taught at Instituto Federal de Educação de Pernambuco- IFPE, based on the following question: how is the subjectivity of these students evident in the chronicle genre? It is a qualitative Field research, with a corpus composed of 50 texts from a sample of 10 chronicles, taking into account, for the analysis, the following chronicle categories: time /space, memory, linguistic materiality. In order based on issues related to students from PROEJA and Professional education this work was supported by Frigotto, Ciavatta and Ramos (2005), Moura (2009), Paiva, J. (2004), Kuenzer (2002), Machado, L. (2006), Machado, M. (2009) and Rummert (2007). Whereas the textual aspects, referring to genres, this dissertation relied on Bakthin (2003), Marcuschi (2001, 2003, 2004) and Brandão (2000); on the issues related to subjectivity, effectively marked in the writing of these subjects, this work was supported by Oliveira (2003), Larrosa (2002, 2010) and Certeau (2009). The result of the analysis of the students‟ writings from PROEJA / IFPE lead to the understanding that the school trajectory of these young people, adults and seniors, they themselves, full of knowledge, often invisible to the teachers‟ eyes as it was developed through everyday experiences, and because of that it is not legitimate, these people rely on "strategies" to make them visible, regarding, especially the aspect of subjectivity that this genre makes it possible to be seen in the text.